The need for improved dermoscopy training in residency: a survey of US dermatology residents and program directors - Parth Patel; Sarika Khanna; Beth McLellan; Karthik Krishnamurthy (Mattioli1885, 2017)
Background: Inadequate dermoscopy training represents a major barrier to proper dermoscopy use. Objective: To better understand the status of dermoscopy training in US residency programs. Methods: A survey was sent to 417 dermatology residents and 118 program directors of dermatology residency programs. Results: Comparing different training times for the same training type, residents with 1-10 hours of dedicated training had similar confidence using dermoscopy in general (p = 1.000) and satisfaction with training (p = .3224) than residents with >10 hours of dedicated training. Comparing similar training times for different training types, residents with 1-10 hours of dedicated training had significantly increased confidence using dermoscopy in general (p = .0105) and satisfaction with training (p = .0066) than residents with 1-10 hours of only bedside training. Lastly, residents with 1-10 hours of dedicated training and >10 hours of dedicated training had significantly increased confidence using dermoscopy in general (p = .0002, p = .2471) and satisfaction with training (p <.0001, p < .0001) than residents with no dermoscopy training at all. Conclusions: Dermoscopy training in residency should include formal dermoscopy training that is overseen by the program director and is possibly supplemented by outside dermoscopy training.